Development Of a Learning Module Based on Religious Moderation Values in the East Lampung Al-Quran Education Park - Herawati, Novita; Aprilia, Nada; Ilmi, Ulul (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
Religious moderation can be internalized from an early age to form a moderate character in society. The Baitul Ibadah Al-Quran Education Park (TPQ) in Braja Indah is a strategic place to teach the values ​​of religious moderation to students, especially considering the ethnic diversity that exists. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model to produce a learning module based on religious moderation. After going through the development stages, the resulting teaching module was declared valid by experts. The assessment shows that the module meets the validation criteria and can be used as effective teaching material. Module Validity: The average score from the validator assessment indicates that the module meets the valid criteria. Module Practicality: The results of the ustadzah assessment show that the module is very practical to use in learning. Module Effectiveness: The percentage of students' learning completion reached 80%, indicating that the module was effective in increasing students' understanding of religious moderation. The development of a Koran Education Park learning module based on the values ​​of religious moderation can increase students' understanding of indicators of religious moderation.